2014
DOI: 10.1200/jop.2013.001210
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Black Box: The Impact of an Oncology Management Program Consisting of Level I Pathways and an Outbound Nurse Call System

Abstract: Implementation of Innovent positively affected patient care in several ways: Fewer ER visits and IPAs occurred, in-patient days decreased, cancer-related use costs were reduced, and on-pathway adherence increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 8 publications
(2 reference statements)
0
42
0
Order By: Relevance
“…Recent studies investigating patients during cancer treatment showed a decrease in emergency room visits and lower cancer-related medical costs [16, 17]. However, no studies are available on the effects of CM on quality of life after completion of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies investigating patients during cancer treatment showed a decrease in emergency room visits and lower cancer-related medical costs [16, 17]. However, no studies are available on the effects of CM on quality of life after completion of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, reaching patients before they present to the ED may be a preferable approach to reducing hospital admissions and enhancing outpatient management. Exponents of the oncology patient-centered medical home have described their experience in reducing acute care utilization [15,16] which is largely based on availability of high-functioning telephone triage services and timely outpatient clinical evaluation for acute complaints [17]. Though promising, the generalizability of these types of interventions remains unproven.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…5,6 Cost savings have been reported in several pilot studies testing the use of clinical decision support and bundled payment models to incentivize the use of cost-effective treatments when equally efficacious regimens exist. 7,8 Other research has demonstrated variation in the use of inpatient services for patients with advanced cancer at the regional level but not doi: 10 at the practice level. 9 Some pilot projects have reported reductions in inpatient utilization through enhanced care management.…”
mentioning
confidence: 98%
“…9 Some pilot projects have reported reductions in inpatient utilization through enhanced care management. 10,11 Stakeholders have emphasized opportunities to produce savings by supporting poorly reimbursed aspects of care, such as care planning, care coordination, and enhanced outpatient services to prevent costly inpatient admissions. 12,13 To our knowledge, no study has yet examined the magnitude of variation at the practice level for key oncology services.…”
mentioning
confidence: 99%